Fetal outcome in deliveries with meconium stained liquor - Vaghela, Hemali Pankajbhai; Deliwala, Kruti; Shah, Parul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Meconium is a dark greenish mass of desquamated cells, mucus, and bile that accumulates in the bowel of a fetus and is typically discharged shortly after birth. Meconium stained amniotic fluid has long been considered to be a bad predictor of fetal outcome. Presence of meconium in amniotic fluid is a potentially serious sign of fetal compromise and associated with poor perinatal outcome. This prospective observational study was undertaken to find out immediate fetal outcome in meconium stained liquor. Methods: Design: prospective study. This study was conducted from January 2014 to June 2014. The study included women with meconium stained amniotic fluid in labor with gestational age >37 completed weeks. Results: Total 100 cases were enrolled. 67% were term patient. Majority of the patients (74%) were in the age group of 21-30 years. Fetal distress occurred in 25% of babies, more in association with thick meconium (13%). Cesarean deliveries were 68%. APGAR scores in first minute was severe (0-3) in 5% and 1% at fifth minute, moderate (4-6) in 8% at first minute and was 4% at fifth minute and mild (7-10) in 86% at first minute and 94% at fifth minute. Admission in neonatal ward was 30% with perinatal mortality of 5%. Conclusions: Meconium stained amniotic fluid was associated with higher rate of cesarean delivery, increased need for neonatal resuscitation, increased rate of birth asphyxia with hypoxic ischemic encephalopathy, meconium aspiration syndrome, hospital admission and mortality. Meconium stained liquor is more commonly associated with PIH, post-datism, oligohydroamnios and DM.